The Impact of Childhood Obesity on Mental Health: A Comprehensive Review - Jan Spychalski; Mikołaj Musiał; Maria Spychalska; Adrianna Dylik; Weronika Gryczyńska; Wiktoria Grochowska; Mikołaj Kaczmarek; Łukasz Krawczak; Hanna Gulaczyk (Quality in Sport)
Introduction: Obesity and overweight are among the main health issues affecting the child population in developed countries today. Excess body weight is observed in 29.7% of boys and 14.3% of girls aged 11 to 16 years. Studies reveal that childhood overweight increases the odds of having mental disorders in adolescence compared to children with a normal body weight.